Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages as well as special clothing for those handling chemicals or acids, working in great heat or among flying sparks or splinters. There are more than a score of industries (including chemical works, electrical generation and transmission, chromium plating, tin-plate and cement works) where special clothes are required by law to be worn as protection against injury or poisoning. In these industries employers must supply overalls, waterproof aprons, leggings, clogs, rubber boots, gloves, goggles, caps or face-guards when the Regulations specify them as needed. In many other trades, however, there are risks which can be guarded against by special clothing; for instance, there are some 15,000 serious accidents to the toes of workers every year, many of which could be avoided if special boots with reinforced toe-caps were worn in factories where heavy weights are handled. Employers should be made to provide, and pay for, protective clothing outside the fairly narrow list of trades where it is now compulsory. Even when protective clothing has been provided, employers often complain that the workers refuse to wear it. This may be because the particular clothing is uncomfortable to use, and it is important that workers' organizations be consulted as to the kind of clothing issued to them. It should be as light as it can be made, while giving proper protection, durable, washable, and, if possible, attractive-looking. Clothing compulsorily provided under special regulations is usually required to be washed once a week, and workers should insist on employers making arrangements for this as a general rule in other trades.* Coupons for Protective Clothing Coupons are required for ordinary protective and industrial clothing, except for certain articles (such as protective gloves stamped "industrial") which are impossible to use outside industry and are specifically exempted. The Board of Trade has decided, however, to issue extra coupons to workers who, because of their occupation, have especially heavy clothing needs. These extra coupons are issued through the Ministry of Labour to employers, who distribute them to the workers concerned. In this way extra coupons have been awarded to *Some excellent designs for clothing are given in a Home Office Welfare Pamphlet, No. 1 (1940), on Protective Clothing for Persons Employed in Factories. 12 21/2049